Effects of microfluidic morphologies on the interfacial microstructure and mechanical properties of Ti3SiC2 ceramic and pure copper brazed joints. Issue 10 (15th May 2023) - Chen, Haiyan; Zhao, Shuai; Nai, Xin; Wang, Qian; Liu, Fenjun; Chu, Qiang; Li, Wenya
Abstract: Brazing is a crucial technology in the field of precision joining. In this work, microfluidic systems with different morphologies were fabricated on the surface of a Ti3 SiC2 ceramic by vapour deposition and fine laser etching. The effects of microfluidics on the microstructure and mechanical properties of the Ti3 SiC2 ceramic and the Cu brazed joints were investigated with SEM, TEM and shear strength tests. The width of the Ag–Cu eutectic zone in the brazing seam varied with the microfluidic morphology, which was attributed to the differences in liquid filler wettability in the different microfluidic systems. The interfacial structure of the joint coated with a Ni metal layer was Cu/Ag–Cu eutectic/Ti5 Si3 +CuTi + TiC + Ti2 Ni + Ni3 Ti/Ti3 SiC2 ceramic. In addition, the highest joint strength realized with microfluidics reached 116.9 MPa, which was 15.4% higher than those of joints brazed with smooth ceramics. This work provides theoretical and technical guidance for the field of precision brazing.